ANALISIS PENGARUH PENGGUNAAN TRANSAKSI NON TUNAI ELEKTRONIK DAN DAYA SUBSTITUSINYA TERHADAP TRANSAKSI TUNAI DI INDONESIA - Delivia Damayanti; Deden Dinar Iskandar; Rahmad Tantawi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2023)
Electronic non-cash transaction is an innovation of payment methods. E-money is one of its popular forms. An electronic non-cash transaction using e-money has more advantages than using cash transaction. These advantages make e-money transaction keep increasing. Currently, the increment in e-money transactions has also been accompanied by a decreament in the amount of cash transaction, even though the nominal is still small. This study aims to analyze the effect of electronic non-cash transaction instruments on cash transaction in Indonesia.The dependent variable in this study is cash transactions, the value of cash transactions in this study uses an approach from data on the amount of Gross Domestic Product (GDP) and the value of non-cash transactions (e-money). The independent variables is electronic non-cash transaction proxied by e-money users, number of reader machines, nominal e-money transactions, nominal clearing transactions, and nominal BI-RTGS transactions as a proxy for electronic non-cash transactions. Macroeconomic factors are also added to this study as independent variables, such as GDP, private consumption expenditure, BI interest rate, and inflation rate. This research uses quantitative methods using time-series data from January 2015 to June 2020. The data analysis method used in this research is the Engle-Grangel cointegration test and the error correction model (ECM).The results of the study shows that the number of users and the nominal of e-money transactions as a proxy for electronic non-cash transactions are able to substitute cash transactions in Indonesia in the long-run. While in the short-run, just the nominal of e-money transaction as a proxy for electronic non-cash transactions are able to substitute cash transactions in Indonesia.